Environmental conflicts and public deliberation arenas around the environmental issue in Argentina - Merlinsky, Maria Gabriela (2017)
The purpose of this work is to analyze the way in which various collective actions have given way to new public deliberation arenas around the environmental issue in Argentina. On the basis of the results of a study on the ''conflict over the pulp mills on the Uruguay River" and the ''conflict over the environmental restoration of the Matanza-Riachuelo River basin," our intention is to delve into a theoretical perspective that takes into account the productivity of these events and to analyze different forms of contagion among public arenas. By presenting the results of the case studies, we will refer to the territorial productivity of environmental conflicts.